1985
DOI: 10.1111/j.2044-8260.1985.tb01330.x
|View full text |Cite
|
Sign up to set email alerts
|

An observational evaluation of the effects of nurse training in behaviour therapy on unstructured ward activities and interactions

Abstract: The effects of a five-day in-service training in behaviour therapy for psychiatric nurses were assessed by naturalistic observations in three NHS long-stay wards. The observations focused on nurses' and patients' independent and interactive behaviours as a function of the course of training, during an unstructured part of the ward programme. A comparison of the behaviourally trained nurses and their colleagues indicated that the training had produced no systematic effect on independent activities and was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…There are many potential measures of the generalization of staff training, and it is consistent with the ecological orientation to examine a wide variety of these, in the expectation that some will show training to have undesirable consequences (Campbell etal., 1982). For example, naturalistic observations of nurses, patients and the interactions between them revealed that following in-service training nurses made more frequent use of punishment and were generally less adequate behavioural engineers than their as yet untrained colleagues (Milne, 1984e). To understand such findings it may again prove valuable to pursue an ecological perspective, since this focuses attention on such nurse-patient interdependencies and contingencies as the patients' "coercion" of the would-be nurse-therapists (Sanson-Fisher and Jenkins, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…There are many potential measures of the generalization of staff training, and it is consistent with the ecological orientation to examine a wide variety of these, in the expectation that some will show training to have undesirable consequences (Campbell etal., 1982). For example, naturalistic observations of nurses, patients and the interactions between them revealed that following in-service training nurses made more frequent use of punishment and were generally less adequate behavioural engineers than their as yet untrained colleagues (Milne, 1984e). To understand such findings it may again prove valuable to pursue an ecological perspective, since this focuses attention on such nurse-patient interdependencies and contingencies as the patients' "coercion" of the would-be nurse-therapists (Sanson-Fisher and Jenkins, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have repeatedly documented low levels of knowledge and competence in behavioural technologies by direct care staff, including nursing staff. [32][33][34][35] Situational factors: the context of psychiatric care in the USA Contexts are culturally and historically situated times and places. The context of experience is the world as persons realize that world by way of interactions and transactions among multiple individuals and multiple proximal and distal systems of values, ideologies, and environmental events.…”
Section: Dispositional Factors: the Reality Of Psychiatric Care In Thmentioning
confidence: 99%
“…Inhibiting factors reported by the trainees included organisational restraints. Other attempts at training nonpsychologists have also found that the skills taught have not transferred to the actual service setting (e.g., Milne, 1985). Part of the problem may rest with the fact that attempts at dissemination which focus only on changing the behaviour of individuals within a service system rather than the behaviour of the system itself, a "bottom-up" approach, ignore political and systemic variables that powerfully shape the behavior of individuals (Bernstein, 1982).…”
Section: Bottom-up Versus Top-down Strategies For Large-scalementioning
confidence: 99%